Effect of nonsteroidal anti-inflammatory drugs (NSAIDs) association on physicochemical and biological properties of tricalcium silicate-based cement - Oliveira, Maria Carolina Guiotti de; Queiroz, Índia Olinta de Azevedo; Machado, Thiago [UNESP]; Garrido, Lorena de Mello Alcântara; Oliveira, Sandra Helena Penha de [UNESP]; Duarte, Marco Antonio Hungaro (FapUNIFESP (SciELO), 2022)
The aim of this study was to investigate the physicochemical and biological properties of an experimental tricalcium silicate-based repair cement containing diclofenac sodium (CERD). For the physicochemical test, MTA, Biodentine and CERD were mixed and cement disc were prepared to evaluate the setting time and radiopacity. Root-end cavity were performed in acrylic teeth and filled with cements to analyze the solubility up to 7 days. Polyethylene tubes containing cements were prepared and calcium ions and pH were measured at 3h, 24h, 72h and 15 days. For the biological test, SAOS-2 were cultivated, exposed to cements extracts and cell proliferation were investigated by MTT assay at 6h, 24h and 48h. Polyethylene tubes containing cements were implanted into Wistar rats. After 7 and 30 days, the tubes were removed and processed for histological analyses. Parametric and nonparametric data were performed. No difference was identified in relation to setting time, radiopacity and solubility. Biodentine released more calcium ion than MTA and CERD; however, no difference between MTA and CERD were detected. Alkaline pH was observed for all cements and Biodentine exhibited highest pH. All cements promoted a raise on cell proliferation at 24h and 48h, except CERD at 48h. Biodentine stimulated cell metabolism in relation to MTA and CERD while CERD was more cytotoxic than MTA at 48h. Besides, no difference on both inflammatory response and mineralization ability for all cement were found. CERD demonstrated similar proprieties to others endodontic cements available.